Reviews about affectivity and standard in representations of health in children form the north-eastern region of Portugal: contributions to Education - Dias, Elisa (Revista Hipótese, 2016)
This paper is a result of an on-going investigation project, as a part of the L.I.F., from University of Coimbra. This essay intent to approach children’s representations of health and illness, through an interpretative analysis that seeks to unveiling the manifestation of standard and affectivity in these childhood constructions. We consider that by interpreting children’s representations of health and illness, one can contribute to decentralization of medical discourse itself.